2023
DOI: 10.1111/febs.17010
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the structure and mechanism of action of computer‐designed mastoparan peptides

Karen G. N. Oshiro,
Carlos D. P. Freitas,
Samilla B. Rezende
et al.

Abstract: Mastoparans are cationic peptides with multifunctional pharmacological properties. Mastoparan‐R1 and mastoparan‐R4 were computationally designed based on native mastoparan‐L from wasps and have improved therapeutic potential for the control of bacterial infections. Here, we evaluated whether these peptides maintain their activity against Escherichia coli strains under a range of salt concentrations. We found that mastoparan‐R1 and mastoparan‐R4 preserved their activity under the conditions tested, including ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…A rich source of antiviral peptides is the venom of certain animals, such as arthropods. Initially isolated from wasp venom, the peptide mast-L has proven to be a promising template for designing new peptides [ 22 , 23 , 37 , 38 ]. The initial assays with the peptides were performed to determine cell viability and the MNTC (CC 20 —Cytotoxic Concentration for 20% of the cell monolayer or 80% of cell viability).…”
Section: Resultsmentioning
confidence: 99%
“…A rich source of antiviral peptides is the venom of certain animals, such as arthropods. Initially isolated from wasp venom, the peptide mast-L has proven to be a promising template for designing new peptides [ 22 , 23 , 37 , 38 ]. The initial assays with the peptides were performed to determine cell viability and the MNTC (CC 20 —Cytotoxic Concentration for 20% of the cell monolayer or 80% of cell viability).…”
Section: Resultsmentioning
confidence: 99%
“…Then, for some peptides, it has been shown that the stabilization of the helical structure plays a primary role in their antibacterial activities (Torres et al, 2018). However, for others, it is the balance between hydrophobicity and the insertion of positive residues on the hydrophilic face rather than the adoption of a helical structure that has a more significant effect on its biological activities (Oshiro et al, 2024;. All this shows the complexity of the delicate balance required between physicochemical properties and structure for the biological activities of AMPs, despite the advances made in the AMPs field and the countless studies of the structure-activity relationship (Edwards et al, 2016;.…”
Section: Mic (Mbc) (μMolmentioning
confidence: 99%